(untitled) (Bangladesh Journal of Medical Science, 2012)
Objective: Both plasma glucose and glycosylated hemoglobin are the recommended tools to diagnose diabetes by the International Expert Committee and World Health Organization (WHO). The aim of this study was to compare these two parameters in the diagnosis of diabetes in a selected group of Bangladeshi subjects. Materials and Methods: This cross-sectional study included 800 subjects attending the outdoor in a tertiary healthcare center during the period of September 2009 to September 2010. Fasting, postprandial (2 hours after glucose load) plasma glucose and HbA1c were measured. Diabetes is defined according to HbA1c and plasma glucose. Subjects were classified into three groups according to HbA1c values (HbA1c: =6.5%, HbA1c: 6.0-6.4% and HbA1c: < 6.0%) and also in the diabetics, prediabetics (IGT+IFG) and nondiabetics by plasma glucose. Results of the HbA1c classified subjects were compared with the plasma glucose classified subjects to see the inequity of classification. Results: Inequity of classification occurred for 11.87% of the total subjects with HbA1c =6.5% but impaired (8.25%) and nondiabetic (3.62%) by plasma glucose; for 10.13% of the subjects with HbA1c: 6.0-6.4% but diabetic (3.25%) and nondiabetic (6.88%) by plasma glucose, and for 8.5% of the total subjects with HbA1c <6.0% but diabetic (1.88%) and impaired (6.62%) by plasma glucose. Concordant classification occurred for 69.5% and inequity of classification occurred for 30.5% of the total study subjects. Conclusion: Inequity of classification of diabetes by HbA1c and plasma glucose is remarkable in the study population. Key words: Plasma glucose; glycosylated hemoglobin; diagnostic criteria of diabetes DOI: http://dx.doi.org/10.3329/bjms.v10i4.9502 BJMS 2011; 10 (4): 284-286